Loss estimation of precast prestressed concrete frame structure with cost-efficient mortise-tenon connection under earthquake - Zhao, Hanxi; Takahashi, Noriyuki (Frontiers in Built Environment, 2025)
The Precast Prestressed Concrete (PCaPC) frame is characterized by minimal inelastic damage and self-centering behavior under seismic loading. It offers a viable alternative to conventional reinforced concrete construction, particularly in high seismic hazard regions. By employing unbonded prestressing tendons to connect precast beams and columns, PCaPC systems enhance structural resilience and reduce residual deformations. However, their widespread adoption has been hindered by high material and labor costs, as well as complex assembly processes. To address these limitations, this study proposes a cost-effective Mortise-Tenon (MT) connection. This connection eliminates the need for grouting and other labor-intensive procedures, simplifying construction and reducing total costs by 13%. A Matlab-based nonlinear time history analysis was conducted to evaluate the structural response and expected repair costs under different seismic hazard levels. A case study on a four-story office building in Sendai, Japan, showed that PCaPC frames with MT connections have lower expected seismic losses and better economic performance than traditional cast-in-situ PC frames. These findings highlight the potential of MT-connected PCaPC systems for enhancing cost efficiency and seismic resilience, supporting their widespread adoption in prefabricated construction in earthquake-prone regions.